Cultural Identities in Sustaining Religious Communities in the Arctic Region: An Ethnographic Analysis on Religiosity from the Northern Viewpoint - Nafisa Yeasmin (Journal of Ethnology and Folkloristics)
Northern countries are facing the challenges of declining human capital, and admitting immigrants, many of whom belong to religious minorities, to satisfy the demand for labour. If northern societies accept multiculturalism and immigrants, they should not disregard the cultures and religious practices (for example, ritual slaughter) of immigrants, as they need to survive and integrate as a minority community in a secular society. However, there is clash between secularism and religions permitting animal slaughter, which is prohibited by some and allowed by other European countries. Community viability and sustainability depend partly on the exercise of community beliefs and ideology that support identity behaviour. This study will present an ethnographic analysis of the religiosity related to ritual slaughter and Muslim cultural identity in the European Arctic region and explore how religious relativism and practice sustain the community and support the overall integration of the Muslim minority in the North.